Libraries as tools for development: a survey of users of Oyo State public library (2003)
The role of the library as a tool for creating life long reading habit in the youth is the focus of this paper. Reading by children and the ability to acquire knowledge from infancy up to adolescence and young adulthood were explored. A study of users of the Oyo State Public Library was carried out using questionnaires and oral interview methods. The findings indicate that majority (82%) of the respondents agreed that inability to read hampers knowledge acquisition in many ways and that reading skills need to be taught very early in life to actually entrench a sustainable and good reading habit Libraries and resource centres, government policies on education and the provision of adequate reading facilities for a/I segments of the populace including the visually impaired and the handicapped will encourage reading which will in turn enhance growth and development of the nation. Recommendations are made on the adoption and implementation of the library hour' in primary and secondary school curricular. Reading and reading skills also need to be taught in schools. "The failure of our schools and colleges, in times past, to teach the practical fundamentals of reading as a life long culture has been a curse to our civilization and development" - Brewer 1846.